PENGARUH FAKTOR FINANSIAL TERHADAP PRESTASI KERJA KARYAWAN PADA AKADEMI MARITIM YOGYAKARTA (AMY) - Suyanti Suyanti (Sekolah Tinggi Maritim Yogyakarta, 2018)
This study examines the influence of financial factors on employee performance at the Yogyakarta Maritime Academy (AMY). The problem studied is the influence of financial factors on employee performance. This research is a quantitative research that uses primary data as its data source. Data were obtained from questionnaires to employees of the Yogyakarta Maritime Academy. Data were analyzed using simple linear regression. The results of the study concluded that there is a significant influence of financial factors on employee performance at the Yogyakarta Maritime Academy (AMY). It can be seen from simple linear regression test that get significance level (Sig) < 0,05. The great influence given by the financial factor on work performance is equal to 0.686 (68.6%). This means that every 10% increase of the financial factor will increase 68.6% employee performance.